Influence of gaseous environment on the properties of Inconel 625 L-PBF parts. (December 2022) - Traoré, S.; Koutiri, I.; Schneider, M.; Lefebvre, P.; Rodrigues, J.; Dupuy, C.; Coste, F.; Peyre, P.
Abstract: The effect of gaseous atmosphere during Laser Powder Bed Fusion (L-PBF) was analysed on an Inconel 625 alloy. The bead dimensions, the surface finish, the porosity rate and the resulting microstructure were analysed for three different gases (Argon, Nitrogen and Helium) in an industrial L-PBF machine, using rather high energy density promoting keyhole welding regime. No clear effect of gas nature on energy coupling was shown when considering fusion beads on L-PBF parts. However, this work shows that gas, and especially helium mostly modifies surface finish, due to a modification of heat dissipation at the interface between the built part and the powder bed. This effect is clearly beneficial for vertical builds but is balanced by a possible and detrimental reduction of surface tensions for inclined and overhanging surfaces. The data presented here indicates a moderate benefit of He and N2 gases on porosity rates at high laser energy, but the as-built microstructures do not exhibit detectable differences, at the scale considered for the analyses (SEM + EBSD). Some physical aspects of the liquid/gas interface are discussed at the end of the paper to explain the observed results.